Incidence and clinical significance of mitral regurgitation in Takotsubo cardiomyopathy - Haghi, Dariusch; Röhm, Stefanie; Süselbeck, Tim; Borggrefe, Martin; Papavassiliu, Theano (Clinical research in cardiology, 2010)
In a previous report, acute mitral regurgitation (MR) was found to indicate the more severe end of the spectrum of Takotsubo cardiomyopathy (TC). The aim of this study was to determine the incidence and clinical significance of acute MR in TC.